L'homophobie - Borrillo, Daniel; Mécary, Caroline (Que sais-je?, 2019)
« L'homophobie est l'attitude d'hostilité à l'égard des homosexuels, hommes ou femmes. Quelles sont ses origines ? Quels sont ses rapports avec les autres formes de stigmatisation et de discrimination ? Comment, et à partir de quels discours, la suprématie hétérosexuelle, ainsi que la dévalorisation corrélative de l'homosexualité, ont-elles été construites ? Existe-t-il une personnalité homophobe? Et par quels moyens peut-on lutter contre cette forme de violence ? »– Quatrième de couverture.
Section: 127 pages ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; droit; histoire et politique; homophobie; hétérosexisme; premier cycle; science politique et droit; soc2014; systèmes d'oppressions; thématiques; violences

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Conférence: «Droit et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Rachel Chagnon, membre de l'Institut de recherches et d'études féministes et professeure au Département des sciences juridiques.
Keywords: amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; europe; féminisme décolonial; histoire du féminisme; intersectionnalité; inégalités; militance; mouvements des femmes*; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sciences juridiques; sociologie; système colonial; systèmes d'oppressions; thématiques

Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

Girlhood interrupted: The erasure of Black girls' childhood - Epstein, Rebecca; Blake, Jamilia J.; González, Thalia (Georgetown Law, Center on Poverty and Inequality, 2017)
This groundbreaking study by the Georgetown Law Center on Poverty and Inequality provides—for the first time— data showing that adults view Black girls as less innocent and more adult-like than their white peers, especially in the age range of 5–14. The report builds on similar results that have emerged from studies of adult perceptions of Black boys. In 2014, for example, research by Professor Phillip Goff and colleagues revealed that beginning at the age of 10, Black boys are more likely than their white peers to be misperceived as older, viewed as guilty of suspected crimes, and face police violence if accused of a crime.1 SNAPSHOT OF THE DATA Compared to white girls of the same age, survey participants perceive that • Black girls need less nurturing • Black girls need less protection • Black girls need to be supported less • Black girls need to be comforted less • Black girls are more independent • Black girls know more about adult topics • Black girls know more about sex These results are profound, with far-reaching implications. Our findings reveal a potential contributing factor to the disproportionate rates of punitive treatment in the education and juvenile justice systems for Black girls.
http://arks.princeton.edu/ark:/88435/dsp01tx31qm28z
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; discipline; droit; fem3300; filles noires; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques; états-unis

(Re)penser l’accès aux espaces intimes en contexte de handicap intellectuel: une question de droit et de participation sociale - Pariseau-Legault, Pierre; Holmes, Dave (Revue générale de droit, 2017)
En contexte de handicap, la question de l’accès est constituée généralement de l’éventail des aménagements individuels et collectifs nécessaires afin de faciliter l’occupation d’espaces publics. A contrario, peu de choses sont dites à propos des aménagements possibles et potentiels requis afin de sécuriser l’espace privé des personnes identifiées comme ayant un handicap intellectuel. Ce sont pourtant ces lieux intimes, au sein desquels se développent et se déploient l’identité et l’expression affectives, qui sont susceptibles de contribuer à une reconnaissance plus soutenue de l’identité affective et de la citoyenneté sexuelle de ces personnes. Inspirée par les théories d’Erving Goffman et de Michel Foucault, une analyse phénoménologique interprétative (API) fut réalisée auprès des personnes ayant un handicap intellectuel et de leurs proches aidants afin d’explorer cette situation. Nos constats préliminaires suggèrent l’existence d’un processus de négociation complexe des acteurs, des lieux et des moments nécessaires afin de favoriser le développement de la vie affective et sexuelle. De ce fait, trois modes d’existence semblent cohabiter au sein d’une matrice complexe : la dépossession, l’habitation et l’occupation des espaces de socialisation et d’expression affective. Il est proposé d’aborder cette problématique en tant que dynamique géopolitique intégrant les processus d’exclusion des pratiques sexuelles des espaces privés, leur projection dans des espaces publics et, finalement, la juxtaposition de ces deux sphères, publique et privée dans des espaces mixtes. Nous discuterons enfin des implications de cette réflexion sur la « question de l’accès » et sur les politiques publiques visant à diminuer la discrimination systémique ciblant les personnes identifiées comme ayant un handicap intellectuel.
Keywords: approches et analyses; capacitisme; care; corps; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; ressource en ligne; santé; science politique et droit; science politique et droit de la santé; sciences; sciences de la santé; sciences politiques; sex1920; sexualité; systèmes d'oppressions; thématiques

Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Normal life: Administrative violence, critical trans politics, and the limits of law - Spade, Dean (Duke University Press, 2015)
Attendez—qu'est-ce qui ne va pas avec les droits ? On suppose généralement que les personnes transgenres et non conformes au genre devraient suivre les stratégies de droits civils et «d'égalité» des organisations de défense des droits des lesbiennes et des homosexuels en faisant campagne pour des réformes juridiques qui garantiraient ostensiblement la non-discrimination et une protection égale devant la loi. Cette approche suppose que la meilleure façon de lutter contre la pauvreté et la criminalisation qui affligent les populations trans est d'obtenir une reconnaissance légale et une inclusion dans les institutions de l'État. Mais cette stratégie est-elle efficace ? Dans la vie normaleDean Spade présente des critiques révélatrices du cadre d'égalité juridique pour le changement social et pointe des exemples d'activisme trans populaire transformateur qui soulève des demandes qui vont au-delà des réformes traditionnelles des droits civiques. Spade explose les hypothèses sur ce que les droits légaux peuvent faire pour les populations marginalisées et décrit les processus et les formations de résistance transformatrice qui s'attaquent aux causes profondes du mal et de la violence. Dans la nouvelle postface de cette édition révisée et augmentée, Spade note l'intégration rapide de la politique trans et constate que ses prédictions selon lesquelles l'obtention d'une reconnaissance légale ne profitera pas aux populations trans se concrétisent. Spade examine les efforts récents de l'administration Obama et des défenseurs de l'égalité des trans pour "pinkwash" la violence d'État en articulant les systèmes militaires et pénitentiaires américains comme des sites pour les réformes d'inclusion des trans. Dans le contexte de la récente visibilité accrue des personnes trans et de la politique trans, Spade continue de plaider pour le démantèlement des systèmes de violence d'État qui raccourcissent la vie des personnes trans. Aujourd'hui plus que jamais, Normal Life est un appel urgent à la justice et à la libération trans, et aux transformations radicales que cela nécessitera.
https://public.ebookcentral.proquest.com/choice/publicfullrecord.aspx?p=2096555
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; droit; fem9000; identités LGBTQIA2+; militance; personnes trans*; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; violences; états-unis

Les oubliés du Code civil du Québec - Caron, Vincent; Berthold, Gabriel-Arnaud; Deslauriers-Goulet, Charlotte; Torres-Ceyte, Jérémie; LeBel, Louis (Les Éditions Thémis, 2014)
À l’occasion du vingtième anniversaire de l’entrée en vigueur du Code civil du Québec – événement symbolique d’importance – , il est apparu opportun d’amorcer une réflexion sur « les oubliés du Code civil », c’est-à-dire des notions qui évoluent en marge de l’œuvre codificatrice. Cet ouvrage a pour objet de faire la lumière sur certaines de ces notions dans une perspective dynamique. Ainsi, autour des principales divisions du Code civil – le droit des personnes, le droit de la famille, le droit des biens et le droit des obligations -, les auteurs offrent leurs réflexions et nourrissent un débat fertile et salutaire sur l’évolution du droit civil au Québec. Préface de Louis LeBel, juge à la Cour suprême du Canada de 2000 à 2014.
Section: xix, 226 pages ; 23 cm
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; québec; régions géographiques; science politique et droit; soc2014; systèmes d'oppressions; thématiques

“It Happened More Than Once”: Freezing Deaths in Saskatchewan - Razack, Sherene (Canadian Journal of Women and the Law, 2014)
Le présent article analyse les enquêtes et une commission sur des décès par hypothermie en Saskatchewan, au Canada. Il souligne les économies raciales et d’espace liées à ces décès, et il suggère que les relations structurelles propres au colonialisme de peuplement produisent et encouragent les expulsions continues et quotidiennes d’autochtones de la part des colonisateurs, expulsions qui sont inévitablement violentes. La ville coloniale appartient au colonisateur et son occupation est inévitablement récusée par la présence des autochtones dans la ville. L’autochtonité met mal à l’aise, car elle conteste la prétention du colonisateur à la légitimité en remettant en cause une fiction très tenace dans les états coloniaux selon laquelle les peuples autochtones seraient à l’agonie. La pratique qui consiste à repousser les autochtones aux périphéries de la ville vient du besoin des colonisateurs de maintenir les lignes de force des villes coloniales. Aujourd’hui, quand cette pratique est scrutée par le droit, comme ce fut le cas dans l’enquête sur le décès de Neil Stonechild, et dans des enquêtes sur les décès par hypothermie, elle est considérée soit comme le fait de quelques policiers sans vergogne ou encore on la nie carrément. Ce qui demeure dans les registres judiciaires, toutefois, ce sont les économies raciales d’espace dans la ville coloniale et la dévalorisation persistante de la vie autochtone, une dévalorisation que la loi produit et soutient. Dans la première partie, je présente des idées sur les économies raciales et d’espace de la ville coloniale. Dans la deuxième partie, j’étudie le cas du décès de Neil Stonechild, ainsi que la réponse du droit à ce décès, la Commission d’enquête Wright. Dans la troisième partie, j’analyse les enquêtes sur les décès par hypothermie de Rodney Niastus et de Lawrence Wegner, deux jeunes autochtones morts dix ans après Stonechild, et j’explore deux mouvements dans l’espace et le temps : Niastus et Wegner traversant la ville pour trouver la mort dans un champ gelé de la zone nord-ouest, et le cheminement que l’enquête nous invite à faire en nous faisant croire que Niastus et Wegner sont les seuls responsables de leur décès. Dans le panorama des décès d’autochtones en détention en Saskatchewan, y compris en prison, par suicide et à la suite de violents affrontements avec la police, le corps d’un autochtone est un corps qui ne peut être assassiné.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; histoire et politique; hypothermie; justice sociale; meurtre; mort; personnes autochtones; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; violences

« Quelque longue que soit l’absence » : procurations et pouvoir féminin à Québec au xviiie siècle - Grenier, Benoît; Ferland, Catherine (Clio. Femmes, Genre, Histoire, 2013)
Dans les sociétés préindustrielles, l’exercice du pouvoir au sein de la famille est étroitement lié aux contingences juridiques et aux normes patriarcales. La connaissance du rôle joué par les femmes dans les activités économiques de la famille, en particulier les femmes mariées, échappe le plus souvent aux historiens. L’étude des procuratrices à Québec, capitale de la Nouvelle-France au xviiie siècle, permet de mieux comprendre le fonctionnement du couple dans un contexte colonial marqué par l’absentéisme masculin. L’analyse des actes de procurations octroyés aux femmes, combinée à une étude prosopographique de nature sociodémographique, révèle les enjeux et les circonstances de ce transfert circonstanciel de pouvoir. Cette voie montre qu’il est possible de contourner partiellement le silence entourant les activités des épouses pour éclairer la délicate question de la complémentarité et de la confiance au sein du couple.
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin https://journals.openedition.org/clio/11053
Keywords: 1600-1699; 1700-1799; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droit; droit des femmes*; his4523; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; maternité; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
https://clio.columbia.edu/catalog/8481765
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Le texte de McKay, M. C. et Benjamin, C. (2010). A vision for fulfilling the indivisible rights of Indigenous women a été donné en lecture au cours POL4105.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences